Lethargy and vision loss: successful management of rhinocerebral mucormycosis. (2nd June 2016) - Mulki, Ramzi; Masab, Muhammad; Eiger, Glenn; Perloff, Sarah
Abstract : Rhinocerebral mucormycosis (RCM) is an angioinvasive fungal infection most often caused by Rhizopus oryzae . It is usually associated with an underlying risk factor and is associated with a poor prognosis. There are no consensus guidelines on the optimal management of this aggressive disease; most management decisions are based on case reports and expert opinion. We report a successfully managed case of RCM in an insulin-dependent diabetic, initially presenting with a change in mental status, rapidly progressing to complete right eye blindness and ophthalmoplegia and complicated by multiple cerebral infarctions and abscesses. We describe the diagnostic approach and various therapeutic interventions undertaken to successfully manage our patient.